Effect of pressure on the microencapsulation of virgin coconut oil by supercritical anti-solvent (SAS) - Hee, Yen Yi; Tan, Chin Ping; Abdul Rahman, Russly; Mohd Adzahan, Noranizan; Chong, Gun Hean (Faculty of Engineering, Universiti Putra Malaysia, 2016)
Virgin coconut oil was microencapsulated with supercritical anti-solvent (SAS) technique. The aim of this study was to evaluate the influence of pressure on the physical properties of the microparticles produced. An oil-in-water emulsion was prepared and then subjected to supercritical anti-solvent process at the temperature of 50°C, feed flow rate of 4ml/min, CO2 flow rate of 150L/h and, pressure ranging from 12-16 MPa. Microparticles produced were evaluated for encapsulation efficiency based on the total oil determined by Rose-Gottlieb method and surface oil. The moisture content of the microparticles was determined using infrared moisture analyzer, flowability was determined by tapping method, and particle size distribution and particle morphology were determined by particle size analyzer and scanning electron microscope respectively. The encapsulation efficiency was positively affected by pressure increasing from 72.72% to 77.04% as the pressure increased whereas the surface oil content was negatively affected by the pressure decreasing from 9.84 % to 8.61 %. Particles with mean particle size ranging from 39.47±13.83 to 59.86±14.69 μm were obtained by varying the process pressure. All the microparticles produced had low moisture content, and low compressibility index indicating stable and free flowing powder. Further, supercritical anti-solvent technique is a highly potential process for the production of functional food ingredients.